In the Folds of the Flesh - Bergonzelli, Sergio; Pacheco, Mario; Rossi Drago, Eleonora; Angeli, Pier; Mayo, Alfredo (Koch Media, 2013)
In a genre defined by shocking violence and psychosexual kink, it remains perhaps the most over-the-top ‘giallo’ in EuroCult history: Former MGM starlet and doomed James Dean paramour Pier Angeli - two decades past her Golden Globe award for "Most Promising Newcomer" and just one year before her tragic death - stars in this ultra-lurid epic packed with decapitations, pet vultures, creepy incest, groovy fashions, cyanide baths, swirly psychedelics, inexplicable plot twists, Nazi death camp flashbacks and more. Eleonora Rossi Drago, Fernando Sancho and Luciano Catenacci co-star in the 1970 sickie that would make Freud himself scream in horror, now fully restored from the original Italian vault elements. [horrornews.net]
Keywords: DVD-Video